2013
DOI: 10.4172/2157-7536.s12-002
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescently-Labeled Estradiol Internalization and Membrane Trafficking in Live N-38 Neuronal Cells Visualized with Total Internal Reflection Fluorescence Microscopy

Abstract: Estradiol is a steroid hormone that binds and activates estradiol receptors. Activation of these receptors is known to modulate neuronal physiology and provide neuroprotection, but it is not completely understood how estradiol mediates these actions on the nervous system. Activation of a sub-population of estradiol receptor-α (ERα), originally identified as a nuclear protein, localizes to the plasma membrane and appears to be a critical step in neuroprotection against brain injury and disease. Previously we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Further studies led us to find that estradiol actually induces endocytosis in breast cancer cells and that it is ERα located at the cell membrane that travels in endosomes to the nucleus (95). Previously, others had shown an association of ERα to the endosomal compartment (96), but induction of endocytosis by estrogens had been only described for neurons (97), to our knowledge. Inhibition of endocytosis by both pharmacological and genetic approaches led to inhibition of ER's transcriptional activity.…”
Section: The Extracellular Matrixmentioning
confidence: 83%
“…Further studies led us to find that estradiol actually induces endocytosis in breast cancer cells and that it is ERα located at the cell membrane that travels in endosomes to the nucleus (95). Previously, others had shown an association of ERα to the endosomal compartment (96), but induction of endocytosis by estrogens had been only described for neurons (97), to our knowledge. Inhibition of endocytosis by both pharmacological and genetic approaches led to inhibition of ER's transcriptional activity.…”
Section: The Extracellular Matrixmentioning
confidence: 83%
“…As for other hormones that bind to membrane receptors ( e.g., receptor tyrosine kinases - RTKs) 17 , E2 induces ERα degradation while it activates intracellular signaling circuitries required for hormone-regulated physiological effects. As a consequence, different investigators have suggested an endocytic trafficking of E2-activated membrane-localized ERα, as it occurs for activated RTKs 16 35 36 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Selectively impermeable estrogen derivatives. GPER Pharmacology to result in ligand internalization through endocytosis (Kisler et al, 2013). Furthermore, an E2-activated process that results in localization of ERa to lysosomes and endosomes as a pathway for degradation was recently reported, identifying that lysosome function was required for E2-dependent cell proliferation but not for ERa-mediated ERE-containing gene transcription (Totta et al, 2014).…”
Section: Membrane-impermeable Estrogen Probesmentioning
confidence: 99%